Karl Rahner’s Notion of Vorgriff - Hoppál, Bulcsú Kál (Verbum – Analecta Neolatina, 2004)
The paper will examine the role of the notion of Vorgriff in Rahner’s thought. Rahner was convinced that man’s nature is being oriented towards God. The meaning of the notion of Vorgriff (’preapprehension’) depicts man as a being who lacks something and whose main characteristic is "world-openness’’. In which sense can one preapprehend being? Is it apprehended in totality, or partly? Is it an explicit or implicit knowledge about being? If we proceed with this motion of the intellect to infinity, how can one, without further ado, identify infinity with God? In the paper, I shall examine the philosophical roots of Rahner’s notion of Vorgriff, as one can find it in Maréchal and Heidegger. In addition, I will show how Rahner reconciles the Kantian challenge with Maréchal and Heidegger. Finally, I will argue that the notion of Vorgriff opens the way of transcendental Thomism towards the Platonic tradition.